Non-native plantations: Plant invasion hotspots to multispecies bridgeheads - Xiaoqiong Li; Daniel Simberloff; Wei Huang (Trends in Ecology & Evolution, 2026)

Invasive animal impacts, management, and controversies - Daniel Simberloff (Biological Invasions, 2026)

Nonnative forestry plantations: invasion epicenters? - Xiaoqiong Li; Daniel Simberloff; Wei Huang (Trends in Ecology & Evolution, 2026)

A different take on managing invasions - Daniel Simberloff (Biological Invasions, 2026)

Intentions matter: Response to Lundgren et al. (2024) - Mark W. Schwartz; Daniel Simberloff (Conservation Biology, 2025)

Revisiting invasional meltdown: mechanisms and consequences of positive non-native species interactions - Anthony Ricciardi; Daniel Simberloff (Biological Invasions, 2025)

Animal personhood meets invasive species management - Daniel Simberloff (Biological Invasions, 2025)

“A kind of metastasizing arthropodal cancer” - Daniel Simberloff (Biological Invasions, 2024)

Reflections on a quarter century of editorial service - Daniel Simberloff (Biological Invasions, 2024)

Yet another call for the end of invasion biology - Daniel Simberloff; Laura A. Meyerson (Biological Invasions, 2024)

Anguished appraisal of eradicating non-native species - Daniel Simberloff (Biological Invasions, 2024)

Deep dive into the biology, ecology, and sociology of a prominent invader - Daniel Simberloff (Biological Invasions, 2024)

A faulty metaphor and frustrating weeding lead to advocacy of non-native plants - Daniel Simberloff; Laura A. Meyerson (Biological Invasions, 2024)

Going up the Andes: patterns and drivers of non-native plant invasions across latitudinal and elevational gradients - Eduardo Fuentes-Lillo; Jonas J. Lembrechts; Agustina Barros; Valeria Aschero; Ramiro O. Bustamante; Lohengrin A. Cavieres; Jan Clavel; Ileana Herrera; Alejandra Jiménez; Paula Tecco; Philip E. Hulme; Martín A. Núñez; et al. (Biodiversity and Conservation, 2023)

Increasing tree invasion on Isla Victoria: 10 years after the original “gringos en el bosque” study - Jaime Moyano; Daniel Simberloff; María Andrea Relva; Martin A. Nuñez (Biological Invasions, 2023)

Wild boar rooting impacts soil function differently in different plant community types - M. Noelia Barrios-Garcia; Marina Gonzalez-Polo; Daniel Simberloff; Aimée T. Classen (Biological Invasions, 2023)

Exploring the performance of Biological Invasions in social media five years after opening its Facebook and Twitter accounts - Ana Novoa; Susan Canavan; Deah Lieurance; Daniel Simberloff; Laura A. Meyerson (Biological Invasions, 2023)

A science-based policy for managing free-roaming cats - Christopher A. Lepczyk; David C. Duffy; David M. Bird; Michael Calver; Dmitry Cherkassky; Linda Cherkassky; Christopher R. Dickman; David Hunter; David Jessup; Travis Longcore; Scott R. Loss; Kerrie Anne T. Loyd; et al. (Biological Invasions, 2022)

Plants in eastern Canada poised to become invasive problems – risks in light of climate change - Daniel Simberloff (Biological Invasions, 2022)

Concise, comprehensive reviews of how invasive plants interact with plants, animals, and microbes - Daniel Simberloff (Biological Invasions, 2022)

Two decades of data reveal that Biological Invasions needs to increase participation beyond North America, Europe, and Australasia - Martin A. Nuñez; Mariana C. Chiuffo; Hanno Seebens; Sara Kuebbing; Matthew A. McCary; Deah Lieurance; Bo Zhang; Daniel Simberloff; Laura A. Meyerson (Biological Invasions, 2022)

A self-study of editorial board diversity at Biological Invasions - Sara E. Kuebbing; Matthew A. McCary; Deah Lieurance; Martin A. Nuñez; Mariana C. Chiuffo; Bo Zhang; Hanno Seebens; Daniel Simberloff; Laura A. Meyerson (Biological Invasions, 2022)

The journal Biological Invasions evolves - Laura A. Meyerson; Daniel Simberloff (Biological Invasions, 2022)

Maintenance management and eradication of established aquatic invaders - Daniel Simberloff (Hydrobiologia, 2021)

History, impacts, and prospects for controlling a bevy of devastating invaders - Daniel Simberloff (Biological Invasions, 2021)

Invasion costs, impacts, and human agency: response to Sagoff 2020 - Ross N. Cuthbert; Sven Bacher; Tim M. Blackburn; Elizabeta Briski; Christophe Diagne; Jaimie T. A. Dick; Franz Essl; Piero Genovesi; Phillip J. Haubrock; Guillaume Latombe; Bernd Lenzner; Yves Meinard; et al. (Conservation Biology, 2020)
Article impact statement : In an era of profound biodiversity crisis, invasion costs, invader impacts, and human agency should not be dismissed.

History, impacts, and management in Africa of the world’s most invasive aquatic plant - Daniel Simberloff (Biological Invasions, 2020)

Invasive plants of eastern Canada: history, impacts, management, and stories - Daniel Simberloff (Biological Invasions, 2020)

State of the art of eradicating island invasives…and much more - Daniel Simberloff (Biological Invasions, 2019)

Variable colonization by the hemlock woolly adelgid suggests infestation is associated with hemlock host species - Christy Leppanen; James A. Fordyce; Anthony V. LeBude; Thomas G. Ranney; Daniel Simberloff (Biological Invasions, 2019)

A tribute to Enrique J. Chaneton - José L. Hierro; Aníbal Pauchard; Martín A. Nuñez; Laura A. Meyerson; Daniel Simberloff (Biological Invasions, 2019)

A case of fallacy in scientific discourse? - Christy Leppanen; Daniel Simberloff (Biological Invasions, 2019)

Media representation of hemlock woolly adelgid management risks: a case study of science communication and invasive species control - Christy Leppanen; David M. Frank; John J. Lockyer; Casey J. Fellhoelter; Anna Killeen Cameron; Bevin A. Hardy; Lucas Jeffrey Smith; Macey R. Clevenger; Daniel Simberloff (Biological Invasions, 2019)

Everything you want to know about stink bugs - Daniel Simberloff (Biological Invasions, 2018)

A case for anole territoriality - Jordan M. Bush; Daniel Simberloff (Behavioral Ecology and Sociobiology, 2018)

Introducing “Alien Floras and Faunas”, a new series in Biological Invasions - Petr Pyšek; Laura A. Meyerson; Daniel Simberloff (Biological Invasions, 2018)

Editorial note - Daniel Simberloff (Biological Invasions, 2018)

Two new French books about invasions - Daniel Simberloff (Biological Invasions, 2018)

Aquaculture expansion in Brazilian freshwaters against the Aichi Biodiversity Targets - Dilermando Pereira Lima Junior; André Lincoln Barroso Magalhães; Fernando Mayer Pelicice; Jean Ricardo Simões Vitule; Valter M. Azevedo-Santos; Mário Luís Orsi; Daniel Simberloff; Angelo Antônio Agostinho (Ambio, 2018)

A new monograph on biological control - Daniel Simberloff (Biological Invasions, 2017)

Two books about Great Lakes invasions - Daniel Simberloff (Biological Invasions, 2017)

Honoring Harold A. Mooney: Citizen of the world and catalyst for invasion science - Daniel Simberloff; Laura A. Meyerson; Petr Pyšek; David M. Richardson (Biological Invasions, 2017)

Removing the abyss between conservation science and policy decisions in Brazil - Valter M. Azevedo-Santos; Philip M. Fearnside; Caroline S. Oliveira; André A. Padial; Fernando M. Pelicice; Dilermando P. Lima; Daniel Simberloff; Thomas E. Lovejoy; André L. B. Magalhães; Mario L. Orsi; Angelo A. Agostinho; Francisco A. Esteves; et al. (Biodiversity and Conservation, 2017)

Introducing “The Elton Reviews,” a new series in biological invasions - Laura A. Meyerson; Daniel Simberloff (Biological Invasions, 2017)

Jodi Frawley and Iain McCalman (eds): Rethinking invasion ecologies from the environmental humanities - Daniel Simberloff (Biological Invasions, 2016)

Jacques Tassin: La grande invasion: Qui a peur des espèces invasives? - Daniel Simberloff (Biological Invasions, 2016)

Possible character displacement of an introduced mongoose and native marten on Adriatic Islands, Croatia - Arijana Barun; Daniel Simberloff; Shai Meiri; Nikola Tvrtković; Zoran Tadić (Journal of Biogeography, 2015)
Aim Character displacement and release can occur quickly in novel environments and communities. Species introductions are ‘natural experiments’ in which evolutionary changes can be studied as community composition varies. We asked whether morphologies of the introduced small Indian mongoose ( Herpestes auropunctatus ) and the larger native stone marten ( Martes foina ) on Adriatic islands where they are sympatric or allopatric are consistent with hypotheses of character displacement and release, respectively. Location The mongoose is native to Asia and has been introduced to over 60 islands. We measured specimens from several island groups and the native region. The marten is native to Eurasia and several European islands, and we have measurements throughout most of its native range. Methods We measured skull length and the maximum diameter of the upper canine tooth in both species on Adriatic islands and compared these traits with those in other sites. Results The mongoose has smaller canines and skulls on the three Adriatic islands it co‐occupies with the marten compared with other islands of introduction, consistent with the hypothesis of character displacement. It is not larger on the Adriatic island where it is the sole carnivore than on other Adriatic islands, which contradicts the hypothesis of character release. Marten skulls are shorter on three islands with no mongooses than on one island where the mongoose is present, consistent with the hypothesis of character release. However, marten canine diameters are similar across Adriatic islands. Main conclusions On Adriatic islands, interspecific competition between the mongoose and the marten is most likely what maintains small size in the mongoose and prevents the character release observed on other islands of introduction lacking mammalian competitors. The marten may have undergone character displacement because of the mongoose introduction on at least one Adriatic island and possibly all three islands where the species co‐occur.

The checkered history of checkerboard distributions: reply - Edward F. Connor; Michael D. Collins; Daniel Simberloff (Ecology, 2015)

Reuben P. Keller, Marc W. Cadotte and Glenn Sandiford (Eds): Invasive species in a globalized world - Daniel Simberloff (Biological Invasions, 2015)

Plant–soil interactions promote co‐occurrence of three nonnative woody shrubs - Sara E. Kuebbing; Aimée T. Classen; Jaime J. Call; Jeremiah A. Henning; Daniel Simberloff (Ecology, 2015)
Ecosystems containing multiple nonnative plant species are common, but mechanisms promoting their co‐occurrence are understudied. Plant–soil interactions contribute to the dominance of singleton species in nonnative ranges because many nonnatives experience stronger positive feedbacks relative to co‐occurring natives. Plant–soil interactions could impede other nonnatives if an individual nonnative benefits from its soil community to a greater extent than its neighboring nonnatives, as is seen with natives. However, plant–soil interactions could promote nonnative co‐occurrence if a nonnative accumulates beneficial soil mutualists that also assist other nonnatives. Here, we use greenhouse and field experiments to ask whether plant–soil interactions (1) promote the codominance of two common nonnative shrubs ( Ligustrum sinense and Lonicera maackii ) and (2) facilitate the invasion of a less‐common nonnative shrub ( Rhamnus davurica ) in deciduous forests of the southeastern United States. In the greenhouse, we found that two of the nonnatives, L. maackii and R. davurica , performed better in soils conditioned by nonnative shrubs compared to uninvaded forest soils, which suggests that positive feedbacks among co‐occurring nonnative shrubs can promote continued invasion of a site. In both greenhouse and field experiments, we found consistent signals that the codominance of the nonnatives L. sinense and L. maackii may be at least partially explained by the increased growth of L. sinense in L. maackii soils. Overall, significant effects of plant–soil interactions on shrub performance indicate that plant–soil interactions can potentially structure the co‐occurrence patterns of these nonnatives.

Where do camels belong? The story and science of invasive species - Daniel Simberloff (Biological Invasions, 2015)

Brian Douglas Cooke: Australia’s war against rabbits: the story of rabbit haemorrhagic disease - Daniel Simberloff (Biological Invasions, 2015)

Islands as model systems in ecology and evolution: prospects fifty years after MacArthur‐Wilson - Ben H. Warren; Daniel Simberloff; Robert E. Ricklefs; Robin Aguilée; Fabien L. Condamine; Dominique Gravel; Hélène Morlon; Nicolas Mouquet; James Rosindell; Juliane Casquet; Elena Conti; Josselin Cornuault; et al. (Ecology Letters, 2015)
The study of islands as model systems has played an important role in the development of evolutionary and ecological theory. The 50th anniversary of MacArthur and Wilson's (December 1963) article, ‘An equilibrium theory of insular zoogeography’, was a recent milestone for this theme. Since 1963, island systems have provided new insights into the formation of ecological communities. Here, building on such developments, we highlight prospects for research on islands to improve our understanding of the ecology and evolution of communities in general. Throughout, we emphasise how attributes of islands combine to provide unusual research opportunities, the implications of which stretch far beyond islands. Molecular tools and increasing data acquisition now permit re‐assessment of some fundamental issues that interested MacArthur and Wilson. These include the formation of ecological networks, species abundance distributions, and the contribution of evolution to community assembly. We also extend our prospects to other fields of ecology and evolution – understanding ecosystem functioning, speciation and diversification – frequently employing assets of oceanic islands in inferring the geographic area within which evolution has occurred, and potential barriers to gene flow. Although island‐based theory is continually being enriched, incorporating non‐equilibrium dynamics is identified as a major challenge for the future.

Herbert H. T. Prins and Iain J. Gordon (eds.): Invasion biology and ecological theory. Insights from a continent in transformation - Daniel Simberloff (Biological Invasions, 2014)

External morphology explains the success of biological invasions - Ernesto Azzurro; Victor M. Tuset; Antoni Lombarte; Francesc Maynou; Daniel Simberloff; Ana Rodríguez‐Pérez; Ricard V. Solé (Ecology Letters, 2014)
Biological invasions have become major players in the current biodiversity crisis, but realistic tools to predict which species will establish successful populations are still unavailable. Here we present a novel approach that requires only a morphometric characterisation of the species. Using fish invasions of the Mediterranean, we show that the abundance of non‐indigenous fishes correlates with the location and relative size of occupied morphological space within the receiving pool of species. Those invaders that established abundant populations tended to be added outside or at the margins of the receiving morphospace, whereas non‐indigenous species morphologically similar to resident ones failed to develop large populations or even to establish themselves, probably because the available ecological niches were already occupied. Accepting that morphology is a proxy for a species' ecological position in a community, our findings are consistent with ideas advanced since Darwin's naturalisation hypothesis and provide a new warning signal to identify invaders and to recognise vulnerable communities.

Rapid evolution and range expansion of an invasive plant are driven by provenance –environment interactions - Rafael D. Zenni; Joseph K. Bailey; Daniel Simberloff (Ecology Letters, 2014)
To improve our ability to prevent and manage biological invasions, we must understand their ecological and evolutionary drivers. We are often able to explain invasions after they happen, but our predictive ability is limited. Here, we show that range expansions of introduced Pinus taeda result from an interaction between genetic provenance and climate and that temperature and precipitation clines predict the invasive performance of particular provenances. Furthermore, we show that genotypes can occupy climate niche spaces different from those observed in their native ranges and, at least in our case, that admixture is not a main driver of invasion. Genotypes respond to climate in distinct ways, and these interactions affect the ability of populations to expand their ranges. While rapid evolution in introduced ranges is a mechanism at later stages of the invasion process, the introduction of adapted genotypes is a key driver of naturalisation of populations of introduced species.

The 100th of the world’s worst invasive alien species - Gloria M. Luque; Céline Bellard; Cleo Bertelsmeier; Elsa Bonnaud; Piero Genovesi; Daniel Simberloff; Franck Courchamp (Biological Invasions, 2014)

Les Invasions Biologiques: un Danger pour la Biodiversité - Daniel Simberloff (Biological Invasions, 2014)

The checkered history of checkerboard distributions - Edward F. Connor; Michael D. Collins; Daniel Simberloff (Ecology, 2013)
To address the idea that the process of interspecific competition can be inferred from data on geographical distribution alone and that evidence from geographical distribution implies an important role for interspecific competition in shaping ecological communities, we reexamine the occurrence of “true checkerboard” distributions among the land and freshwater birds in three Melanesian archipelagoes: Vanuatu, the Bismarck Archipelago, and the Solomon Islands. We use the most recently published distributional records and explicitly include the geography of the distributions of species within each archipelago. We use the overlap of convex hulls to estimate the overlap in the geographic range for each pair of species in each of these archipelagoes. We define a “true checkerboard” to consist of a pair of species with exclusive island‐by‐island distributions, but that have overlapping geographical ranges. To avoid the “dilution effect,” we follow Diamond and Gilpin in focusing only on congeneric and within‐guild species pairs as potential competitors. Few, if any, “true checkerboards” exist in these archipelagoes that could possibly have been influenced by competitive interactions, and even “true checkerboards” can arise for reasons other than interspecific competition. The similarity between related species pairs (congeneric and within‐guild pairs) and unrelated species pairs in their deviation from expectation of the number of islands shared and the overlap of their geographic ranges indicates that these are not distinct statistical populations, but rather a single population of species pairs. Our result, which is based on an examination of the distributional data alone, is consistent with the interpretation that, in these avifaunas, the distributions of congeneric, within‐guild, and unrelated species pairs are shaped by a common set of biological and physical environmental processes.

Can genetic data confirm or refute historical records? The island invasion of the small Indian mongoose (Herpestes auropunctatus) - Arijana Barun; Matthew L. Niemiller; Benjamin M. Fitzpatrick; James A. Fordyce; Daniel Simberloff (Biological Invasions, 2013)

Number of source populations as a potential driver of pine invasions in Brazil - Rafael Dudeque Zenni; Daniel Simberloff (Biological Invasions, 2013)

Editor’s note - Daniel Simberloff (Biological Invasions, 2013)

Overestimation of establishment success of non-native birds in Hawaii and Britain - Mariano A. Rodriguez-Cabal; Mark Williamson; Daniel Simberloff (Biological Invasions, 2013)

Revisiting the Potential Conservation Value of Non‐Native Species - Jean Ricardo Simões Vitule; Carolina A. Freire; Diego P. Vazquez; Martin A. Nuñez; Daniel Simberloff (Conservation Biology, 2012)

Risks of biological control for conservation purposes - Daniel Simberloff (BioControl, 2012)

Restoring the oceanic island ecosystem: impact and management of invasive alien species in the Bonin Islands - Daniel Simberloff (Biological Invasions, 2012)

The natives are restless, but not often and mostly when disturbed - Daniel Simberloff; Lara Souza; Martín A. Nuñez; M. Noelia Barrios-Garcia; Windy Bunn (Ecology, 2012)
The argument that the threat posed by introduced species is overblown is often buttressed by the observation that native species sometimes also become invasive. An examination of the literature on plant invasions in the United States shows that six times more nonnative species have been termed invasive than native species, and that a member of the naturalized nonnative pool is 40 times more likely than a native species to be perceived as invasive. In the great majority of instances in which a native plant species is seen as invasive, the invasion is associated with an anthropogenic disturbance, especially changed fire or hydrological regime, livestock grazing, and changes wrought by an introduced species. These results suggest that natives are significantly less likely than nonnatives to be problematic for local ecosystems.

William Stolzenburg: Rat Island: Predators in paradise and the world’s greatest wildlife rescue - Daniel Simberloff (Biological Invasions, 2012)

T. C. Boyle: When the killing’s done - Daniel Simberloff (Biological Invasions, 2011)

How common are invasion-induced ecosystem impacts? - Daniel Simberloff (Biological Invasions, 2011)

R.N. Reed and G.H. Rodda (eds): Giant constrictors: biological and management profiles and an establishment risk assessment for nine large species of pythons, anacondas, and the boa constrictor - Daniel Simberloff (Biological Invasions, 2010)

The Indian brown mongoose, yet another invader in Fiji - Geraldine Veron; Marie-Lilith Patou; Daniel Simberloff; Patricia A. McLenachan; Craig G. Morley (Biological Invasions, 2010)

Introduced deer reduce native plant cover and facilitate invasion of non-native tree species: evidence for invasional meltdown - María Andrea Relva; Martin A. Nuñez; Daniel Simberloff (Biological Invasions, 2010)

J. A. Lockwood: Six-Legged Soldiers - Daniel Simberloff (Biological Invasions, 2009)

G.W. Witmer, W.C. Pitt, and K.A. Fagerstone (eds): Managing Vertebrate Invasive Species - Daniel Simberloff (Biological Invasions, 2009)

Non-indigenous land and freshwater gastropods in Israel - Uri Roll; Tamar Dayan; Daniel Simberloff; Henk K. Mienis (Biological Invasions, 2009)

Lack of belowground mutualisms hinders Pinaceae invasions - Martin A. Nuñez; Thomas R. Horton; Daniel Simberloff (Ecology, 2009)
Why particular invasions succeed and others fail is not well understood. The role of soil biota has been proposed as important. However, the role of mutualists has received much less attention than that of pathogens. Here we report that lack of adequate ectomycorrhizal fungi hinders invasion by exotic Pinaceae on Isla Victoria, Argentina, by reducing both the probability of establishment and growth of invading individuals. More than one hundred exotic tree species were introduced to this island ca. 80 years ago, but invasive trees are found in high densities only in areas adjacent to plantations. With a series of greenhouse and field experiments we found lower mycorrhizal colonization levels and few fungal species far from original plantings, and key fungal mutualists are confined to areas near plantations, probably owing to dispersal limitations. Low inoculum levels far from the plantations are retarding the invasion. Our experiments indicate that positive interactions belowground can play a key but underappreciated role in invasion dynamics.

Rats are not the only introduced rodents producing ecosystem impacts on islands - Daniel Simberloff (Biological Invasions, 2009)

Habitat use and potential interactions between the house mouse and lesser white-toothed shrew on an island undergoing habitat restoration - Michel Pascal; Olivier Lorvelec; Frédéric Bioret; Pierre Yésou; Daniel Simberloff (Mammal Research, 2009)

Rarefaction and nonrandom spatial dispersion patterns - Michael D. Collins; Daniel Simberloff (Environmental and Ecological Statistics, 2009)

W. van der Weijden, R. Leewis, P. Bol, Biological Globalisation. Bio-invasions and their Impacts on Nature, the Economy, and Public Health. - Daniel Simberloff (Biological Invasions, 2009)

Ecosystem-level consequences of invasions by native species as a way to investigate relationships between evenness and ecosystem function - Loïc Valéry; Hervé Fritz; Jean-Claude Lefeuvre; Daniel Simberloff (Biological Invasions, 2009)

R. B. Allen and W. G. Lee (eds): Biological Invasions in New Zealand - Daniel Simberloff (Biological Invasions, 2009)

Global change and carnivore body size: data are stasis - Shai Meiri; Dorit Guy; Tamar Dayan; Daniel Simberloff (Global Ecology and Biogeography, 2009)
Aim Global warming and other anthropogenic changes to the environment affect many aspects of biology and have often been invoked as causing body size changes in vertebrates. Here we examine a diverse set of carnivore populations in search of patterns in body size change that could reflect global warming (in accord with Bergmann's rule). Location Global. Methods We used > 4400 specimens representing 22 carnivore species in 52 populations collected over the last few decades to examine whether size changed with collection date when geography and sex are accounted for. We then examined several factors related to global warming, body mass, diet, and the attributes of the different datasets, to see whether they affect the standardized slope (β) of the size versus time regression. Results Six of 52 populations we examined show a significant effect of year of collection on body size at the 0.05 probability level. The response of size to global warming does not reflect spatial patterns of size variation, nor do diet or body mass affect tendency of populations to change in body size. Size changes are no more pronounced in populations that have been sampled more recently. However, change, where it occurs, is rapid. Main conclusions There may be a tendency in the literature to report only cases where recent changes are prevalent. Although in our data only a minority of populations show body size changes, we may see changes accelerating in the future in response to more drastic climatic changes and other anthropogenic changes.

Introduction of non‐native freshwater fish can certainly be bad - Jean Ricardo Simões Vitule; Carolina Arruda Freire; Daniel Simberloff (Fish and Fisheries, 2009)
In this paper, we respond to Gozlan’s views of the introduction of freshwater fish, as we strongly disagree with his view and approach. We demonstrate that many real‐world examples of freshwater fish introductions have catastrophic ecological consequences. We detail a few noteworthy examples, such as those of the Nile perch, carp, tilapias, catfishes, and the zebra mussel. We discuss within‐nation introductions, and we explore several related problems, such as hybridization and spread of pathogens and parasites. We propose that Gozlan’s analysis is biased, as more reliable data on impacts that are already widespread are urgently needed, mainly in the biologically richest areas of the world. Thus, we continue to advocate the precautionary principle, because species introductions, once established, are largely irreversible.

We can eliminate invasions or live with them. Successful management projects - Daniel Simberloff (Biological Invasions, 2009)

In search of a real definition of the biological invasion phenomenon itself - Loïc Valéry; Hervé Fritz; Jean-Claude Lefeuvre; Daniel Simberloff (Biological Invasions, 2008)

Seed predation as a barrier to alien conifer invasions - Martin A. Nuñez; Daniel Simberloff; Maria Andrea Relva (Biological Invasions, 2008)

Non-indigenous terrestrial vertebrates in Israel and adjacent areas - Uri Roll; Tamar Dayan; Daniel Simberloff (Biological Invasions, 2008)

Mining and Other Threats to the New Caledonia Biodiversity Hotspot - MICHEL PASCAL; BERTRAND RICHER DE FORGES; HERVÉ LE GUYADER; DANIEL SIMBERLOFF (Conservation Biology, 2008)

Invasive Species in the Pacific Northwest - Daniel Simberloff (Biological Invasions, 2008)

Guild composition and mustelid morphology – character displacement but no character release - Shai Meiri; Tamar Dayan; Daniel Simberloff (Journal of Biogeography, 2007)
Aim Competition is hypothesized to lead to the evolution of reduced morphological overlap between competitors. Within guilds, this is believed to lead to overdispersed size ratios of the trophic apparatus of adjacent‐sized species. In allopatry, conditions are believed to favour character release. We examined whether character displacement is prevalent in mainland musteline guilds and sought evidence for character release in adjacent island guilds. Location Holarctic, from Japan through western Europe to Pacific North America. Methods We measured skulls and canines of members of the mustelid subfamily Mustelinae and examined whether size ratios tend towards equality. We then examined whether insular guilds are characterized by larger size ratios and a higher degree of sexual size dimorphism than mainland guilds, and whether this reflects evolution towards the size of missing guild members. Results We found equal ratios between skull lengths but not canine diameters in all mainland guilds. Few insular guilds showed equal ratios for either trait. There was scant evidence for character release: insular mustelines do not evolve towards the size of a missing guild member, nor is sexual size dimorphism greater on islands. There was no evidence for a lower limit on the size similarity of co‐existing mustelids. Main conclusions We propose that different guild compositions in different localities produce different evolutionary trajectories. Similar sizes on islands and mainlands can be explained by similar prey sizes in both settings. Morphological evidence suggests that competition is probably not a ubiquitous force in the assembly and evolution of musteline guilds.

Peter A. Coates, American Perceptions of Immigrant and Invasive Species. Strangers on the Land - Daniel Simberloff (Biological Invasions, 2007)

Characteristics of the introduced fish fauna of Israel - Uri Roll; Tamar Dayan; Daniel Simberloff; Menachem Goren (Biological Invasions, 2007)

Non-indigenous insect species in Israel and adjacent areas - Uri Roll; Tamar Dayan; Daniel Simberloff (Biological Invasions, 2007)

Alfred E. Hartemink, Invasion of Piper aduncum in the Shifting Cultivation Systems of Papua New Guinea - Daniel Simberloff (Biological Invasions, 2007)

S. Elmendorf, J. Byrnes, A. Wright, S. Olyarnik, R. Fischer, and L. Chamberlin, Fear and Fishing in Lake Davis (DVD) - Daniel Simberloff (Biological Invasions, 2007)

Systematic status and biogeography of the Javan and small Indian mongooses (Herpestidae, Carnivora) - Geraldine Veron; Marie‐Lilith Patou; Geraldine Pothet; Daniel Simberloff; Andrew P. Jennings (Zoologica Scripta, 2007)
The Javan and small Indian mongooses, ranging from the Middle East to South‐east Asia, are considered as two species or as a single species, varying in size and colour from west to east. In order to clarify their systematic status and to define the limits of their ranges, Cytochrome b sequences were obtained from 27 specimens, and localities of 392 specimens from museum collections were determined. The phylogenetic analyses revealed that the Javan and Small Indian mongooses grouped in two separate clades with their range limits located in Myanmar. The Javan mongoose is in fact closer to the grey mongoose than to the small Indian mongoose.

Genetic divergence in the small Indian mongoose ( Herpestes auropunctatus ), a widely distributed invasive species - CARL‐GUSTAF THULIN; DANIEL SIMBERLOFF; ARIJANA BARUN; GARY MCCRACKEN; MICHEL PASCAL; M. ANWARUL ISLAM (Molecular Ecology, 2006)
The combination of founder events, random drift and new selective forces experienced by introduced species typically lowers genetic variation and induces differentiation from the ancestral population. Here, we investigate microsatellite differentiation between introduced and native populations of the small Indian mongoose ( Herpestes auropunctatus ). Many expectations based on introduction history, such as loss of alleles and relationships among populations, are confirmed. Nevertheless, when applying population assignment methods to our data, we observe a few specimens that are incorrectly assigned and/or appear to have a mixed ancestry, despite estimates of substantial population differentiation. Thus, we suggest that population assignments of individuals should be viewed as tentative and that there should be agreement among different algorithms before assignments are applied in conservation or management. Further, we find no congruence between previously reported morphological differentiation and the sorting of microsatellite variation. Some introduced populations have retained much genetic variation while others have not, irrespective of morphology. Finally, we find alleles from the sympatric grey mongoose ( Herpestes edwardsii ) in one small Indian mongoose within the native range, suggesting an alternative explanation for morphological differentiation involving a shift in female preferences in allopatry.

Book Review - Daniel Simberloff (Biological Invasions, 2006)

The generality of the island rule reexamined - Shai Meiri; Tamar Dayan; Daniel Simberloff (Journal of Biogeography, 2006)
Aim M.V. Lomolino and colleagues have recently reviewed the island rule in mammals and other vertebrates, claiming it is a general pattern. They have portrayed our recent analysis as weakly supporting the island rule, seeing weakness in our use of what they considered to be inadequate size indices (skulls and teeth, rather than mass or body length) and in our use of large islands. They argue that size evolution on islands points to a bauplan‐specific fundamental size. We aim to test the generality of the rule and the adequacy of some of the data used to support it. Location Insular environments world‐wide. Methods We collate and analyse data on skull sizes of carnivores and body masses of mammals in general to see whether there is a graded trend from dwarfism in large species to gigantism in smaller ones. Results The island rule is not supported with either the carnivore or the mammal data sets. Island area does not influence size change. Main conclusions Our results suggest that data recently advanced in support of the island rule are inadequate and that the island rule is not a general pattern for all mammals.

Invasional meltdown 6 years later: important phenomenon, unfortunate metaphor, or both? - Daniel Simberloff (Ecology Letters, 2006)
Cases in which introduced species facilitate one another's establishment, spread, and impacts are increasingly noted, and several experimental studies have provided strong evidence of a population‐level impact. However, a full ‘invasional meltdown’, in which interspecific facilitation leads to an accelerating increase in the number of introduced species and their impact, has yet to be conclusively demonstrated. The great majority of suggested instances of ‘invasional meltdown’ remain simply plausible scenarios of long‐term consequences based on short‐term observations of facilitatory interactions between individuals of two species. There is a particular dearth of proven instances in which two invasive species each enhance the impact and/or probability of establishment and spread of the other. By contrast, in many authenticated cases, at least one partner is aided. The metaphor of meltdown focused attention on facilitation in invasion and has probably helped inspire recent studies. As have other metaphors from invasion biology and other sciences, ‘meltdown’ has struck a responsive chord with writers for the lay public; some have stretched it well beyond its meaning as understood by invasion biologists. There is no evidence that this hyperbole has impeded scientific understanding or caused loss of scientific credibility.

Rejoinder to Simberloff (2006): Don't calculate effect sizes; study ecological effects - Daniel Simberloff (Ecology Letters, 2006)

Book Review: The Fire Ant Wars. By Joshua Blu Buhs, 2004, 216 pp, University of Chicago Press, Chicago, US$22.50, ISBN 0-226-07982-1. - Daniel Simberloff (Biological Invasions, 2006)

Area, isolation and body size evolution in insular carnivores - Shai Meiri; Tamar Dayan; Daniel Simberloff (Ecology Letters, 2005)
Body sizes of insular mammals often differ strikingly from those of their mainland conspecifics. Small islands have reduced numbers of competitor and predator species, and more limited resources. Such reductions are believed to select for predictable changes in body sizes, with large mammals growing progressively smaller as island area decreases, while small ones grow progressively larger. Medium‐sized mammals are thought to be largest on intermediate‐sized islands. Increased isolation is seen as promoting insular gigantism. We searched for such patterns using a large database of insular carnivore specimens. Neither small nor large carnivores show a consistent area/body size relationship. Medium‐sized carnivores are no more likely to attain large size on medium‐sized islands then they are to be small there. We found no consistent patterns of body size variation in relation to isolation.

Ecological and community‐wide character displacement: the next generation - Tamar Dayan; Daniel Simberloff (Ecology Letters, 2005)
Ecological character displacement, mostly seen as increased differences of size in sympatry between closely‐related or similar species, is a focal hypothesis assuming that species too similar to one another could not coexist without diverging, owing to interspecific competition. Thus, ecological character displacement and community‐wide character displacement (overdispersion in size of potential competitors within ecological guilds) were at the heart of the debate regarding the role of competition in structuring ecological communities. The debate has focused on the evidence presented in earlier studies and generated a new generation of rigorous, critical studies of communities. Character displacement research in the past two decades provides sound statistical support for the hypothesis in a wide variety of taxa, albeit with a phylogenetically skewed representation. A growing number of studies are strongly based in functional morphology, and some also demonstrate actual morphologically related resource partitioning. Phylogenetic models and experimental work have added to the scope and depth of earlier research, as have theoretical studies. However, many challenging ecological and evolutionary issues, regarding both selective forces (at the inter‐ and intraspecific level) and resultant patterns, remain to be addressed. Ecological character displacement and community‐wide character displacement are here to stay as the focus of much exciting research.

Out of Eden. An Odyssey of Ecological Invasion. By Alan Burdick, 2005, 325 pp, 4 figures. Farrar, Straus and Giroux, New York.Hardback: 25, ISBN 13: 978-0-374-21973-4. - Daniel Simberloff (Biological Invasions, 2005)

Biogeographical patterns in the Western Palearctic: the fasting‐endurance hypothesis and the status of Murphy's rule - Shai Meiri; Tamar Dayan; Daniel Simberloff (Journal of Biogeography, 2005)
Aim In Europe, winter severity is positively correlated with longitude. We test how this climatic cline affects biogeographical patterns in Western Palearctic homeotherms. Location Eurasia, west of 60° longitude. Methods We test the effects of longitude on body size of carnivores, using cranial measurements of 2002 specimens belonging to 11 species. We test the effects of longitude on migration patterns of birds by comparing which populations of partial migrants are sedentary and which undergo winter migration. Results Carnivore body size does not vary consistently with longitude. Populations of partial migrants are more likely to be sedentary in western Europe and to migrate from eastern Europe than vice versa. Main conclusions Longitudinal patterns in climate exert a selective force on birds but do not affect carnivore size in a consistent, predictable manner. We find no support for the mechanism suggested to promote size change, namely the fasting‐endurance hypothesis.

Book Reveiw: Ecology and Control of Introduced Plants - Daniel Simberloff (Biodiversity and Conservation, 2004)

Now you See them, Now you don't! – Population Crashes of Established Introduced Species - Daniel Simberloff; Leah Gibbons (Biological Invasions, 2004)

Changes in interaction biodiversity induced by an introduced ungulate - Diego P. Vázquez; Daniel Simberloff (Ecology Letters, 2003)
Long‐term conservation of biodiversity may depend not only on the maintenance of its component parts but also on their interactions. Here we provide strong evidence that an introduced species is able to affect the network of interactions among coexisting species. We studied plant–pollinator interactions in native forest sites with and without domestic cattle and used these data to construct plant–pollinator interaction networks. Results from nonmetric multidimensional scaling and permutation tests suggest that the presence of cattle has significantly modified the structure of the plant–pollinator interaction network. The effect of cattle on network structure was mainly because of the modification of a few highly frequent interactions, which are likely important from a functional perspective. This overwhelming influence of a few interactions on observed community patterns should serve as a caution to those studying community and ecosystem properties.

Confronting introduced species: a form of xenophobia? - Daniel Simberloff (Biological Invasions, 2003)

Introduced Species and Management of a Nothofagus/Austrocedrus Forest - DANIEL SIMBERLOFF; MARIA ANDREA RELVA; MARTIN NUEZ (Environmental Management, 2003)

How Much Information on Population Biology Is Needed to Manage Introduced Species? - Daniel Simberloff (Conservation Biology, 2003)
Study of the population biology of introduced species has elucidated many fundamental questions in ecology and evolution. Detailed population biological research is likely to aid in fine‐tuning control of widespread and/or long‐established invasions, and it may lead to novel control methods. It will also contribute to an overall understanding of the invasion process that may aid in the formulation of policy and help to focus attention on invasions that are especially prone to becoming problematic. But the importance of intensive population biological research in dealing with introduced species, especially those recently introduced, is often limited. In the worst instances, the absence of population biological data can be an excuse for inaction, when a prudent decision or quick and dirty operation might have excluded or eliminated an invader. The most effective way to deal with invasive introduced species, short of keeping them out, is to discover them early and attempt to eradicate or at least contain them before they spread. This approach has often been successful, but its success has usually relied on brute‐force chemical and mechanical techniques, not on population biological research.

Random binary matrices in biogeographical ecology—Instituting a good neighbor policy - Arif Zaman; Daniel Simberloff (Environmental and Ecological Statistics, 2002)

Book review: A Plague of Rats and Rubbervines. The Growing Threat of Species Invasions. - Daniel Simberloff (Biological Invasions, 2002)

Gringos En El Bosque: Introduced Tree Invasion in a Native Nothofagus/Austrocedrus Forest - Daniel Simberloff; María Andrea Relva; Martín Nuñez (Biological Invasions, 2002)

How Many, And Which, Plants Will Invade Natural Areas? - Julie L. Lockwood; Daniel Simberloff; Michael L. McKinney; Betsy Von Holle (Biological Invasions, 2001)

Feral Future. The Untold Story of Australia's Exotic Invaders - Daniel Simberloff (Biodiversity and Conservation, 2001)

Book review - Daniel Simberloff (Biodiversity and Conservation, 2000)

Positive Interactions of Nonindigenous Species: Invasional Meltdown? - Daniel Simberloff; Betsy Von Holle (Biological Invasions, 1999)

Biological Invasions - Daniel Simberloff (Biodiversity and Conservation, 1998)